Education Management Strategies to Maximize the Effectiveness of Information and Communication Technology Integration in Teaching and Learning Processes - Siminto; Almaududi Ausat, Abu Muna; Rijal, Syamsu (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The integration of Information and Communication Technology (ICT) has become a key factor in driving this change. This research aims to elucidate educational management strategies to maximize the effectiveness of integrating information and communication technology in the teaching and learning process. The research method used in this study is a literature review with a qualitative approach. Data sources are derived from Google Scholar for the period 2004-2024. This research utilizes Google Scholar as the primary source to obtain relevant, credible, original, and publicly available articles for systematic analysis. The study results indicate that in the era of Information and Communication Technology (ICT) development, the integration of ICT in education is crucial to enhance learning effectiveness. To achieve this, focused and comprehensive educational management strategies are highly important. These strategies should be based on a strong understanding of the role of ICT in learning, integration of ICT into the curriculum, training and support for educators and students, development of technological infrastructure, development of supportive policies, inclusive and sustainable approaches in ICT strategy development, as well as collaboration among educational institutions, government, industry, and the community